Brand value in horizontal alliances: the case of twin-cars - Esteban-Bravo, M; Lado, N (The Journal of the Operational Research Society, 2011)
Rival firms often cooperate horizontally in order to share risks and achieve scale advantages in production or in their research and development projects. The output of these strategic alliances is usually sold by the individual ally company under its own brand and using its own marketing mix strategies. Marketing strategies create a cumulative effect that is reflected in brand value. Although horizontal alliances often have a significant overall impact on firm profitability, undesired brand value dilution is a worrisome possibility for the partners and therefore a relevant subject of study. In this paper, we consider brand value to be the economic added value of a brand, and propose two market-based measures of brand value: (1) price premia (which are relevant for a unit sale) and (2) revenue premia (which also account for the premia in sales volume). We apply this analysis to the Spanish market for new automobiles, in which successful and long-lasting horizontal alliances have formed. Our findings suggest that, during the introduction stage of the product life cycle, horizontal allies did not charge different price premia, but that horizontal allies profit from differences in brand reputation obtained from demand side effects such as revenue premia (specifically, the impact on sales volume). Consequently, horizontal cooperation among brands does not dilute their value at the introduction stage. Furthermore, our results suggest that horizontal allies do charge different price premia during the growth stage of the product life cycle. Consequently, horizontal allies have recognized strategies that do not dilute brand value in intense competition mitigating the brand value diluting risk.